2016
DOI: 10.1016/j.amsu.2016.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial salmonella with cardiac tamponade and ventricular wall rupture: A case report

Abstract: IntroductionNon-typhoidal Salmonella (NTS) is mostly restricted to gastroenteritis; however, we report a case of Salmonella pericarditis complicated by tamponade and spontaneous ventricular wall rupture.Case presentationA 67-year-old male presents to the Emergency Department with complaints of fevers, chills and body aches. A chest radiograph displayed an infiltrate and an electrocardiogram suggested acute pericarditis. An echocardiogram revealed a small pericardial effusion without tamponade. Broad-spectrum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Invasive disease can have serious end organ damage including pericardial seeding resulting in cardiac tamponade and ventricular wall rupture [9], endocarditis, and arthritis [10]. Salmonella bacteremia is treated with monotherapy for 10 -14 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive disease can have serious end organ damage including pericardial seeding resulting in cardiac tamponade and ventricular wall rupture [9], endocarditis, and arthritis [10]. Salmonella bacteremia is treated with monotherapy for 10 -14 days.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella responds well to fluoroquinolones and thirdgeneration cephalosporins which are the preferred drug classes in the United States. However, there are reports of emerging resistance to the fluoroquinolones worldwide [10]. In developing countries, azithromycin is the preferred empirical treatment and can be combined with ceftriaxone for life-threatening situations.…”
Section: Discussionmentioning
confidence: 99%
“…In this modern antibiotic era, the prevalence of purulent pericarditis and pleuritis are rare. Based on the literature review pertaining to salmonellosis with purulent pericarditis, only four reported cases have been published so far 9–12. To the best of the researchers’ knowledge, this is the first reported case of salmonellosis involving pericardial and pleural empyema in Malaysia.…”
Section: Introductionmentioning
confidence: 94%
“…Purulent pericarditis is rare in the modern antibiotic era and it is commonly caused by Gram-positive bacteria, which tend to directly spread from an intrathoracic focus ( 1 , 2 ). Although Salmonellosis, an infection due to Salmonella bacteria, is common worldwide, Salmonellae are rarely reported as causative agents of purulent pericarditis ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…An altered immune response in patients with uncontrolled diabetes mellitus is recognized to lead to an increased risk of multiple types of infections ( 5 ). However, only three reported cases of associated purulent pericarditis have so far been published based on our review of the pertinent literature ( 3 , 4 ). We herein report an unusual case of pericarditis caused by Salmonella enterica subspecies arizona ( S. enterica subsp.…”
Section: Introductionmentioning
confidence: 99%